Phosphatase and Tensin Homolog Mutation in Immune Cell Infiltration and Clinicopathological Features of Low-Grade Gliomas - Feng, Peng; Li, Zhenqing; Li, Yuchen; Zhang, Yuelin (Frontiers in Molecular Biosciences, 2020)
The mutation of phosphatase and tensin homolog (PTEN) genes frequently occur in low-grade gliomas (LGGs) and are deeply associated with a poor prognosis and survival rate. In order to identify the crucial signaling pathways and genes associated with the PTEN mutation, we performed bioinformatics analysis on the RNA sequencing results, which were obtained from The Cancer Genome Atlas database. A total of 352 genes were identified as differentially expressed genes (DEGs). The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis suggested that the DEGs were significantly enriched in categories associated with cell division and multiple metabolic progressions. The histological stage was significantly associated with PTEN expression levels. In addition, the PTEN mutation was associated with an abundance of B cells, neutrophils, macrophages, dendritic cells, and CD8+ T cells during tumor infiltration. The results showed that patients with LGGs harboring the PTEN mutation had a poor prognosis and more serious immune cell infiltration occurred depending on the mRNA expression level. These results demonstrated that multiple genes and signaling pathways play a key role in LGG from low grade to high grade, and are associated with PTEN mutations. In this study, we outlined an approach to assess the influence of PTEN mutations on prognosis, overall survival, and messenger RNA (mRNA) expression. Our results provided alternative strategies for the personalized treatment of patients with LGGs harboring the PTEN mutation.